Combating Corruption Through Anti-Corruption Education: Shaping Integrity, Awareness, and Critical Capacity in Society - ManArfa, Arman (JENDELA PENGETAHUAN, 2023)
Facing the complexity and dynamics of contemporary society, the threat of corruption has become a concerning issue, jeopardizing sustainability and impeding progress. Corruption not only affects the public sector but also infiltrates various aspects of social life. Anti-corruption education emerges as a crucial solution to build integrity, raise awareness of the risks of corruption, and cultivate critical capabilities to navigate situations related to corruption. This article depicts the urgency of anti-corruption education in addressing the adverse impacts of corruption on society and the nation. This educational approach not only imparts theoretical understanding but also shapes character, fosters ethical values, and sharpens critical skills to combat corruption. With a focus on the root causes and consequences of corruption, this education encourages active participation of the community in paradigm shifts and aids in addressing the structural and economic challenges faced by the nation. Through collaboration among the government, educational institutions, and the community, anti-corruption education holds the potential to shape a society of integrity, high culture, and active involvement in effective corruption prevention